Celebrating Virtually - Stocker, Shannon (Ann Arbor, Michigan : Cherry Lake Publishing, 2021)
"The COVID-19 pandemic introduced many changes into children's lives. Celebrating Virtually gives actionable suggestions to help young readers adapt and learn to celebrate big moments in new ways as we navigate the current outbreak. This book includes science content, based on current CDC recommendations, as well as social emotional content to help with personal wellness and development of empathy. All books in the 21st Century Junior Library encourage readers to think critically and creatively, and use their problem-solving skills. Book includes table of contents, sidebars, glossary, index, and author biography"--Provided by publisher.
Includes index
Grades 2-3
Keywords: Internet -- Social aspects; Telecommunication -- Social aspects